Aortic Aneurisms - Cobra, Giovana Jacobsen; Garcia, Carolyn Burgos; Neves, Pedro Juan Furtado; Abreu, Phillipe; Jaldin, Rodrigo Gibin [UNESP]; Malgor, Rafael (Springer Nature, 2025)
The prevalence of abdominal aortic aneurysm (AAA) has been increasing in the last years mainly due to the aging of the population and the improvement and diffusion of diagnostic methods [1]. About 80% of aortic aneurysms (AAA) are located below the renal arteries. The main complications of aortic aneurysms are rupture and death, embolization, thrombosis, fistulization, and compression of neighboring structures, such as the ureter and lumbar spine. It is usually asymptomatic and its first diagnostic manifestation can be a rupture. Thus, it is up to the surgeon to know the risk factors for the development of AAA and make an early diagnosis. Major studies such as the Aneurysm Detection and Management Veterans Affairs Cooperative Study Group (ADAM) Trial [2] have identified factors associated with a higher prevalence of AAA, as can be seen synthetically in Table 69.1. Smoking stands out, with AAA being seven times more common in smokers than in nonsmokers [3]. The risk of rupture was assessed in several studies, especially the United Kingdom Small Aneurysm Trial (UKSAT) [4], which are considered factors independently associated with rupture, summarized in Table 69.1.